Development of an occupational advice intervention for patients undergoing lower limb arthroplasty (the OPAL study) - Baker, Paul; Coole, Carol; Drummond, Avril; McDaid, Catriona; Khan, Sayeed; Thompson, Louise; Hewitt, Catherine; McNamara, Iain; McDonald, David; Fitch, Judith; Rangan, Amar (BIOMED, 2018)
Background: There are an increasing number of patients of working age undergoing hip and knee replacements. Currently there is variation in the advice and support given about sickness absence, recovery to usual activities and return to work after these procedures. Earlier, sustainable, return to work improves the health of patients and benefits their employers and society. An intervention that encourages and supports early recovery to usual activities, including work, has the potential to reduce the health and socioeconomic burden of hip and knee replacements. Methods/design: A two-phase research programme delivered over 27 months will be used to develop and subsequently test the feasibility of an occupational advice intervention to facilitate return to work and usual activities in patients undergoing lower limb arthroplasty. The 2 phases will incorporate a six-stage intervention mapping process: Phase 1: Intervention mapping stages 1–3: 1 Needs assessment (including rapid evidence synthesis, prospective cohort analysis and structured stakeholder interviews) 2 Identification of intended outcomes and performance objectives 3 Selection of theory-based methods and practical strategies Phase 2: Intervention mapping stages 4–6: 4 Development of components and materials for the occupational advice intervention using a modified Delphi process 5 Adoption and implementation of the intervention 6 Evaluation and feasibility testing The study will be undertaken in four National Health Service (NHS) hospitals in the United Kingdom and two Higher Education Institution. Discussion: OPAL (Occupational advice for Patients undergoing Arthroplasty of the Lower limb) aims to develop an occupational advice intervention to support early recovery to usual activities including work, which is tailored to the requirements of patients undergoing hip and knee replacements. The developed intervention will then be assessed with a specific focus on evaluating its feasibility as a potential trial intervention to improve speed of recovery to usual activities including work.